XR serious game platform to promote behaviour change - Nuno Filipe Amaral Oliveira (2023)
Brain-computer interfaces (BCI) are a growing technology that can passively monitor brain activity, translating it into actions. The use of this technology, together with Extended Reality (XR) applications, is yet in its initial stage, and although promising, it is still untested. The correct use of XR in educational environments can play a significant role in developing critical thinking and problem-solving abilities and even help the social integration of learners. In this dissertation, we propose to create a serious game application for behaviour change in an educational environment. With careful consideration of existing knowledge on game mechanics, game design, persuasive strategies and immersive technology regarding their advantages and disadvantages, the game will be pedagogic while stimulating the general cognitive development of children. The application's behaviour change goals are boosting attention and motivation when learning, and increasing social communication and integration, all while facilitating knowledge acquisition. The platform will also present itself as a very relevant tool for educators by displaying learning analytics, through which they can better understand each learner's learning process and results. The application is to be later incorporated into a BCI environment for monitoring brain activity, the evolving cognitive patterns associated with behaviour change and using haptic technology for learning purposes. For such a piece of software to be created, we first need to study the central XR and ludic methodologies in the existing knowledge base for games created for similar educational and persuasive motivations. Furthermore, the role of different immersive technologies, and learning analytics solutions also require investigation. Serious games take advantage of several cognitive advantages inherent to video games and can outperform traditional instructional methods in terms of motivation, behaviour learning and knowledge retention outcomes. XR technology in a learning environment is highly responsible for raising learners' interest and motivation, increasing learning rates and knowledge retention duration. Learning analytics can be helpful to various stakeholders of serious educational games (players, teachers and researchers) and have an essential role in complementing some game mechanics and understanding the players' learning behaviours. The resulting game will be heavily inspired by the classic board game 'Battleship'. The game will be designed towards educational usage and extend a physical board through Augmented Reality technology. The game's main mechanic will be representations of historic naval battles where players will face each other with ship models that resemble their natural-world counterparts.